Building the Commercial Education Professional Competency Profile - Araya Muñoz, Isabel (2012)
This paper provides a complete description of the Commercial Education Professional Competency Profile that resulted from the curricular diagnosis of the Licenciatura en Educación Comercial , at the Universidad Nacional, Costa Rica.  The methodological strategy used relies on the principles of research on education. Upon expert validation, written questionnaires were applied to first-year students, students of the licenciatura, practicing professionals and employers. The objective was to describe a particular education situation. Data was analyzed according to two categories: intentions/principles and scope/development. The findings resulted in the characteristics of the Commercial Education professionals, i.e. characteristics related to the discipline, characteristics related to the administrative management of teaching, specific and general characteristics of education and pedagogy, and characteristics associated to human development. Based on those criteria, on the curricular requirements of the information sources and on the curricular perspectives of the Academic Unit, ideas were put into practice to build the competency profile. The ideas proposed comprise the curricular fundamentals of the educational project on which the profile is set out, which include the subject of the study program, the global competency or training goal, the generic competencies as cross-cutting approaches, as well as the –pedagogical and disciplinary− specific competencies. The specific competencies of the discipline are focused on four competency areas: document production, organizational support, technological resources and information management. (1) Translator’s Note: One-year post-Bachelor study program in Commercial Education.